Protective efficacy of intranasal inactivated pseudorabies vaccine is improved by combination adjuvant in mice - Hua, Tao; Chang, Chen; Zhang, Xuehua; Huang, Yuqing; Wang, Haiyan; Zhang, Daohua; Tang, Bo (Frontiers in Microbiology, 2022)
Pseudorabies virus (PRV) not only causes great economic loss to the pig industry but also seriously threatens the biosafety of other mammals, including humans. Since 2011, PRV mutant strains have emerged widely in China, and the classical Bartha-K61 vaccine cannot confer complete protection for pigs. PRV mainly infects pigs via the respiratory tract. Intranasal immunization with PRV has received more attention because intranasal vaccination elicits systemic and mucosal immune responses. To induce systemic and mucosal immune responses against PRV, we developed a combination adjuvant as a delivery system for intranasal vaccine, which was formulated with MONTANIDE™ GeL 01 and CVCVA5. In comparison to naked antigen of inactivated PRV, single GeL 01 adjuvanted inactivated antigen and single CVCVA5 adjuvanted inactivated antigen, intranasal inactivated PRV vaccine formulated with the combination adjuvant induced greater mucosal IgA immunity and serum antibody responses (IgG, IgG1 and IgG2a). Furthermore, the production of the Th1-type cytokine IFN-γ and the Th2-type cytokine IL-4 indicated that the cellular and humoral responses to the intranasal vaccine were improved by the combination adjuvant. In addition, the intranasal vaccine formulated with the combination adjuvant induced long-term T lymphocyte memory with increased central (CD62L+CD44+) and effector (CD62L-CD44+) memory subsets of both CD4 and CD8 T cells in nasal-associated lymphoid tissue. Intranasal challenge with virulent PRV in mice showed that the protective efficacy of the intranasal PRV vaccine was improved by the combination adjuvant compared with the other single-adjuvanted vaccines. In summary, these data demonstrated that Gel 01 combined with the CVCVA5 adjuvant induced a synergistic effect to improve mucosal immunity and protective efficacy of the intranasally inactivated PRV vaccine in mice. It represents a promising vaccination approach against PRV infection.